The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/eea.13020
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of the leaf‐cutting ant Atta bisphaerica by phorid flies: biology and seasonal and inter‐colonial parasitism rates

Abstract: The leaf-cutting ant Atta bisphaerica Forel (Hymenoptera: Formicidae, Attini) forages leaves from monocotyledons in natural environments and is a serious pest of pastures and sugarcane plantations in Brazil. This study investigated aspects of the interactions between A. bisphaerica and dipteran Phoridae parasitoids. The seasonal and inter-colonial variations in parasitism rates were also investigated. Ants from four A. bisphaerica colonies were sampled, with a total of 91 554 worker ants collected and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…The distribution of phorid parasitism, when considering the four parasitoid species studied here, showed that attacks by A. attophilus were the most frequent (46%). This result was similar to that seen in previous studies of A. laevigata and also for other species of leaf-cutting ants such as A. sexdens and A. bisphaerica [22,66,68,69]. In fact, the ability of A. attophilus to cause high levels of mortality differentiated it from other species of parasitoids.…”
Section: Plos Onesupporting
confidence: 91%
See 4 more Smart Citations
“…The distribution of phorid parasitism, when considering the four parasitoid species studied here, showed that attacks by A. attophilus were the most frequent (46%). This result was similar to that seen in previous studies of A. laevigata and also for other species of leaf-cutting ants such as A. sexdens and A. bisphaerica [22,66,68,69]. In fact, the ability of A. attophilus to cause high levels of mortality differentiated it from other species of parasitoids.…”
Section: Plos Onesupporting
confidence: 91%
“…In the current study, an average of three A. attophilus (ranging from one to fourteen parasitoids) emerged from each host forager ant, whilst the other three species of phorids had a solitary habit, laying only one egg in each host insect. These characteristics highlight the potential of A. attophilus as a biological control agent against leaf-cutting ants [66,68]. Also in the current study, foragers that had been parasitized by A. attophilus had the shortest survival time (2.8 days) following collection in the field.…”
Section: Plos Onesupporting
confidence: 58%
See 3 more Smart Citations